PERLINDUNGAN HUKUM TERHADAP SAKSI INSTRUMENTER DALAM AKTA NOTARIS YANG AKTANYA MENJADI OBJEK PERKARA PIDANA DI PENGADILAN - LIZA DWI NANDA (PREMISE LAW JURNAL, 2016)
An instrument witness has to give his testimony correctly according to what he has witnessed during the reading of a deed in the court’s proceedings about the true legal act in the deed, the presence of litigants, and their identity. The research used judicial normative method with legal statute approach. The result of the research showed that the presence of a witness is the principal prerequisite to make the deed authentic. A witness’ position is very important in a notarial affair, and he gets protection in giving his testimony about a deed with legal problem. Law No. 31/2014 on the amendment of Law No. 13/2006 on Protection for Witness and Victim gives legal protection for witness during his testimony in the proceedings. Keywords: Instrument Witness, Notary, False Testimony